(untitled) (Journal Of Educational and Psychological Researches, 2014)
Keeping the secret itself of topics for values ​​are positive attribute of personality traits balanced. Objective of this research study of Keeping the secret when spouses, the study of the theory based on the research and literature that dealt with the subject study is important to mention that there was no study of one Iraqi addressed the study of Keeping the secret when spouses. The researcher found the importance of the study of it’s Keeping the secret when spouses. the factors that affect family relationships in terms of the stability of the marital relationship and this is reflected positively on the lives of family and community. Of the recommendations of the research, the adoption of the educational aspect about Keeping the secret when spouses to keep the family entity, which is reflected in the community Asagrar. The researcher suggests further studies on the topic of Keeping the secret when spouses and its relationship with other variables such as life satisfaction, marital sexuality.